KAJIAN STRATEGI PEMASARAN DALAM MENGHADAPI ERA DISRUPSI TEKNOLOGI DI MASA PANDEMI COVID 19 PADA KOPERASI SUSU KUD SARWA MUKTI - Erpurini, Wala; Alamsyah, Nur (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2021)
This community service is carried out at KUD Sarwa Mukti which is a dairy cooperative. The purpose of this community service is to conduct a study of the marketing strategy used by this cooperative in the era of technological disruption during the covid-19 pandemic. The method used in this community service is a qualitative descriptive method. The participation of members of the â€œSARWA MUKTIâ€ Village Unit Cooperative (KUD) is given formally which can assist in every decision making. In contributive participation, residents can make their contribution in the form of providing dairy milk or fresh milk which is regulated by the management of the Village Unit Cooperative (KUD) "SARWA MUKTI" itself which is taken from several villages. The Village Unit Cooperative (KUD) â€œSARWA MUKTIâ€ only supplies factories such as PT. ULTRA JAYA. So that this activity is expected to provide an increase in production.